Psychological intervention in some hospitalary-adaptation problems and in a substance-induced psychotic disorder experienced by an acute myeloid leukaemia inpatient - Cruzado, Juan Antonio; Barbero, Javier; Peralta, Virginia B.; Gulini, Martina (Psicooncología, 2010)
Hemato-oncological diseases involve some physical, psychological, emotional and social impacts producing individual and global suffering. Preventive psychological interventions minimize stress and provide adaptation and well-being by empowering patient resources and increasing control perception. In this article we expose an acute myeloid leukaemia inpatient, whose experience of psychophysiological distress stemmed from a lack of social support, from adaptation problems and from scarce understanding of medical information as well as from consecutive risks of worsening in health. After overcoming gradually different threatening situations, some positive changes in selfconcept, in the interpersonal relationships and in his own philosophy of life occurred. This led the patient to a better adaptation to the illness. In conclusion, the main goal of the therapeutic intervention does not only deal with decreasing the negative impact of the disease or tackling the psychopathological difficulties but also helping the patient to use his best strategies to improve well-being.